2020
DOI: 10.47067/reads.v6i2.213
|View full text |Cite
|
Sign up to set email alerts
|

Human Development, Political Stability and Economic Growth: The way forward

Abstract: Economic growth has been known to foster human development for long term economic stability. The evidence of bi-causality in the human development and economic growth nexus is however limited. This paper builds on the reverse causality between human development and economic growth in context of Pakistan, with the moderating impact of political stability. The study applies OLS and VECM on the data collected from World Bank Database from year 2006 to 2018. Our findings exhibit empirical evidence related to endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some publications that have used the stability indicator defined by the World Bank have applied it to countries and specific themes. For example, in Pakistan there is a causal relationship between human development and economic growth, which is moderated by political stability (Khan, 2020); or in the Arab countries, political stability encourage foreign investments (Abdul Rahman, 2020). A particular application of this indicator in the Middle East and North of Africa showed that there is a positive relation between political stability and inflation, that is, higher political stability contributes to higher inflation, which is contrary to the expectation (Samimi, 2012).…”
Section: Part 1: Time Domain Analysismentioning
confidence: 99%
“…Some publications that have used the stability indicator defined by the World Bank have applied it to countries and specific themes. For example, in Pakistan there is a causal relationship between human development and economic growth, which is moderated by political stability (Khan, 2020); or in the Arab countries, political stability encourage foreign investments (Abdul Rahman, 2020). A particular application of this indicator in the Middle East and North of Africa showed that there is a positive relation between political stability and inflation, that is, higher political stability contributes to higher inflation, which is contrary to the expectation (Samimi, 2012).…”
Section: Part 1: Time Domain Analysismentioning
confidence: 99%